Milícia e vida cívica no pensamento de Maquiavel - Vitor Coelho Lima (2016)
The deal of this work is to show how texts underexplored by the tradition as The Art of War of Machiavelli and Della Milizia of Leonardo Bruni allow us to understand a transition to a new way of life and a new philosophy that features Renaissance. Motivated by the instability of Italian politics, also by war and mainly by the growing of the usage of mercenary troops these books absorb not only the urgent need about discussing military affairs but also were inserted in a politic movement of ideas in Florence: the civic humanism. An intellectual movement that promoted republicanism and civic life. The texts acquired a character of practical projects about reformation of the military institutions which had as main guideline to establish a link between the exercise of citizenship and the military service so that the armies become self-sufficient and no more ensure its power through mercenary troops. Our hypothesis is that the study of these texts together shows the development of humanism throughout the centuries of Renaissance focusing in its continuities and in its breakpoints as also points to the main reasons of the civic and politic accent that embodied this movement as the time passed by and allow us to talk about breakpoints in a broad view of philosophy history that attempts to understand Renaissance. It is not my intention to say that this is the only way to study Renaissance republicanism even because there are countless sources. But certainly this approach through the military affair that aims to link the soldiers to the civic life as the citizens to the military life is underexplored and very productive once clarifies not only the republican reasons that are behind this idea and the nature of the relation between humanists and the classic antiquity but mainly analyses the importance of the passage from the contemplative life to the active life as the distinctive mark of Renaissance.